Mental Illnesses and Stigma among Medical Undergraduates in India - Semanti Das; Sunom Merab Lepcha; Ashish Pundhir; Senthil Amudhan (Ubiquity Press, 2024)
The current Medical Education system of India, with its enormous workload and academic demands tend to cause the medical students stress. There is evidence showing medical students at a higher risk of depression, anxiety and burnout compared to other Indian students. Despite, the huge reported numbers, the proportion of students and doctors who seek help for their problems is alarmingly low. One of the reasons provided for the same is stigma towards mental health and an apprehension regarding labels and treatment history on the careers of the students. Increased awareness and with a National Health Programme catered towards mental health, there has been a boost in the utilization and provision of mental health services but it rarely translates into better mental health facilities for the healthcare providers. The special set of challenges faced by a medical students are gradually being recognized and efforts are being made to address them. Curriculum guidelines, teaching methods, student welfare centres and helplines have been the areas of intervention. There should also be changes in approaches towards the students who face problems and providing a safe environment for them to discuss their problems, including encouraging peer support. Thus, a fine balance needs to be present between ensuring the protection of the mental health of a medical student and ensuring a quality medical education for them. Further exploration to address stigma and building empathy among the students and evaluation of the intervention methods devised to address the same becomes very necessary to ensure fruitful interventions. It is the need of the hour to help Indian Medical students overcome their struggles with mental health.